La religion populaire est-elle une légende du XIXe siècle? - Hubert, Ollivier (Histoire sociale / Social History, 2003)
The novel L'influence d'un livre by Philippe Aubert de Gaspé junior, published in 1937, blurred the “modern” categories of science, religion, and superstition, and in so doing constituted a critique of the establishment of a social hierarchy based in part on the domination of official scientific and religious culture. The author’s questioning of authority extended to pushing other limits in validating a religious culture existing outside the formal institution. The novel presents an untidy image, without clear boundaries between what belonged to the religion of the church and what to makeshift, invention, appropriation, word of mouth, or popular acceptance. One must consider L'influence d'un livre as a valid indicator of various apsects, practices, and representations, but especially of the social dynamic that is usually inherent in culture and that is so difficult for the historian to grasp. The novel allows us a better perception of a “religion” with much wider horizons than can be presumed from clerical sources.